Genocídio da juventune negra: uma configuração do racismo - Andrade, Julio Cezar de [UNIFESP] (2019)
This, the present work seeks to investigate the genocide of black youth with the objective of analyzing racism and its impacts on Brazilian socioeconomic formation and contemporaneity, from the neighborhoods chosen in the East Zone: Cidade Tiradentes, Guaianases, Lajeado and Itaim Paulista. It is a quantitative and qualitative bibliographical and documentary research, for an approximation of the reality, that seeks the relation of the deaths with the racism. Priority was given to data from the Youth Development Report (2007), the Map of Violence (2018), and the Brazilian Institute of Geography and Statistics (IBGE) (2010), in the territories surveyed. among others to give elements and subsidies for the research. The research chose as hypothesis the insufficiency of public policies, aimed at the youth, is one of the factors that raises the level of violence, leading to deaths resulting from police actions or trafficking.